Um estudo sobre a estruturação da componente curricular História da Matemática em cursos de licenciatura em Matemática no Instituto Federal do Maranhão - COSTA, Letícia Baluz Maciel (2024)
This research has as its main objective, to investigate Pedagogical Projects of Mathematics Degree Courses (PCP), from the Federal Institute of Education, Science and Technology of Maranhão - IFMA, the way the history of mathematics is structured and presented in these documents. In this sense, we sought to understand the history of mathematics as a essential field of study for the early formation of the math teacher, characterize the history of mathematics as vital knowledge for this formation and to elaborate a classification for the subject of Mathematics History, presented in these PCP. This study is based on the need for the insertion of the History of Mathematics in a broader way, that takes into account Social Aspects of Mathematical education, Epistemological aspects of Mathematics development, and Didactic aspects of teaching. A qualitative, bibliographic, documentary and descriptive research was conducted. Initially, seven campuses of the institution that offer the degree course in Mathematics, in-person and regular modality, from which the course projects were sought. Data analysis uses methods of discursive textual analysis, which has assisted in the creation of four categories of analysis: General Aspects of the History of Mathematics, Summary of disciplines, Objectives and Bibliographic References signaled in the documents. It was observed that there is an appreciation in all structured categories for the classifications that concern the Epistemological Aspects of the History of Mathematics and Social Aspects of the History of Mathematical education, showing that the projects of analyzed courses were shown with little allusions to a History of Mathematics focused on classroom practice.